Pelatihan kewirausahaan berbasis teknologi pada kelompok wirausaha perempuan Pimpinan Daerah Aisyiyah Karanganyar - Utomo, Fahman Hadi; Rizkiawan , Ilham; Khasanah , Aulia Uswatun (Nur Science Institute, 2024)
Marketing is one of the keys to success in running a business. In the modern era, marketing can not only be done in conventional ways but must also be supported in modern ways, namely technology or science and technology-based. Changes and developments in the world of science and technology currently greatly influence all aspects of our lives. In other words, science and technology are essential for human life today and in the future. One of the potentials of science and technology that can be exploited is the potential of information technology. Information technology offers many benefits for users, namely increasing productivity and marketing. Social media is an information technology that is currently developing rapidly and has excellent potential. The solution for service activities in holding technology-based entrepreneurship training for the Aisyiyah Karanganyar Regional Leadership Women's Entrepreneurial Group is to be able to market products more online. We hope that the PDA Karanganyar women's entrepreneurial group can keep up with developments in the era of digitalization so that they can market products more practically and efficiently.